Strategy of Implementing Green Networking in Computer Networks at Bandung Technology University - Muchamad Rusdan (LP2M Universitas Widyatama, 2023)
This research aims to identify and analyze strategies for implementing green networking on BTU computer networks. The research methods used include literature studies, surveys, and interviews with various stakeholders at BTU, as well as analysis of energy usage data from existing computer network infrastructure. This study investigates various technical and operational aspects of implementing green networking, including appropriate technology, implementation strategies, and challenges faced. The research results show that implementing green networking at BTU can reduce energy consumption and operational costs, as well as support the global commitment to reduce greenhouse gas emissions. However, the main challenges faced include initial investment costs, the need for increased technical skills, and resistance to change. Based on the research findings, it provides practical recommendations for BTU to implement green networking effectively, including increasing awareness and education about green networking, investing in environmentally friendly technology, and developing policies and procedures that support sustainability. We anticipate that this research will significantly contribute to environmental preservation, enhance BTU operational efficiency, and serve as a model for other educational institutions to adopt sustainable technological practices.